PERANCANGAN PORTAL INFORMASI GAMPONG PADA GAMPONG LAMBEUGAK KECAMATAN KUTA COT GLIE ACEH BESAR - Munawir Munawir; Erdiwansyah Erdiwansyah (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
The development of information technology is increasingly rapid, so the need for information is also increasingly needed by everyone. Considering the need for information, it is certain to make a system as an information provider in a village called the village information portal. This study aims to design and implement an information portal as an information provider media in Lambeugak village. In this information portal presents the profile of the village, the composition of the village organization, village activities and village information, both announcements and other information. It is expected that with the results of the study in the form of a portal system as a media provider of information, the villagers easily get information about the village, so that important news can be accessed by everyone.